The effects of the COVID-19 pandemic on dengue cases in Malaysia - Md Iderus, Nuur Hafizah; Singh, Sarbhan Singh Lakha; Ghazali, Sumarni Mohd; Zulkifli, Asrul Anuar; Ghazali, Nur Ain Mohd; Lim, Mei Cheng; Ahmad, Lonny Chen Rong Qi; Md Nadzri, Mohamad Nadzmi; Tan, Cia Vei; Md Zamri, Ahmed Syahmi Syafiq; Lai, Chee Herng; Nordin, Nur Shuhada; et al. (Frontiers in Public Health, 2023)
Background Globally, the COVID-19 pandemic has affected the transmission dynamics and distribution of dengue. Therefore, this study aims to describe the impact of the COVID-19 pandemic on the geographic and demographic distribution of dengue incidence in Malaysia. Methods This study analyzed dengue cases from January 2014 to December 2021 and COVID-19 confirmed cases from January 2020 to December 2021 which was divided into the pre (2014 to 2019) and during COVID-19 pandemic (2020 to 2021) phases. The average annual dengue case incidence for geographical and demographic subgroups were calculated and compared between the pre and during the COVID-19 pandemic phases. In addition, Spearman rank correlation was performed to determine the correlation between weekly dengue and COVID-19 cases during the COVID-19 pandemic phase. Results Dengue trends in Malaysia showed a 4-year cyclical trend with dengue case incidence peaking in 2015 and 2019 and subsequently decreasing in the following years. Reductions of 44.0% in average dengue cases during the COVID-19 pandemic compared to the pre-pandemic phase was observed at the national level. Higher dengue cases were reported among males, individuals aged 20–34 years, and Malaysians across both phases. Weekly dengue cases were significantly correlated (ρ = −0.901) with COVID-19 cases during the COVID-19 pandemic. Conclusion There was a reduction in dengue incidence during the COVID-19 pandemic compared to the pre-pandemic phase. Significant reductions were observed across all demographic groups except for the older population (>75 years) across the two phases.